Japanese work ethics : a study of a Japanese engineering company in Malaysia - Mark, Gau. (2002)
The reason for his undertaking is to examine the source of ethnical thinking Japanese's corporate culture and settings. As such, research will focus on a number of deep-rooted traditional eastern teachings and philosophies which has been deemed to have had fundamental influences. It will therefore look at how that source is transferred to the business environment for the promotion of ethnical behaviour.